Foreign Aid and the Question of Fungibility - Pack, Howar; Pack, Janet Rothenberg (The Review of Economics and Statistics, 1993)
This paper analyzes whether the foreign assistance provided for specific categories of expenditure is shifted among them, contrary to the wishes of donors. It also considers whether aid reduces the tax effort of recipient governments. Econometric results are presented for the Dominican Republic that show that the fungibility of aid has resulted in a thwarting of the intentions of donors. An attempt is made to account for the observed differences in behavior of individual countries in altering expenditures. Copyright 1993 by MIT Press.